The Biogeographic Origins of Novelty-Seeking Traits - Erkan Gören (University of Oldenburg, Department of Economics, 2014)
This paper empirically investigates the biogeographic determinants of the human DRD4 exon III locus, a particular gene variant associated with the human personality trait of novelty-seeking behavior. Providing a novel compilation of worldwide DRD4 exon III allele frequencies in a large sample of indigenous populations around the world, this study employs population-specific biogeographic characteristics using hig h-resolution geospatial data. The estimates suggest that migratory distance from East Africa naturally selects for specific novelty-seeking traits, even controlling for a broad range of biogeographic determinants. Notably, land suitability for pastoral nomadism is significantly related to DRD4 exon III diversity. This result provides further credence to the general observation that novelty-seeking traits are quite common in nomadic populations, explaining why some societies failed to settle and to develop centralized states.
Keywords: N50; O10; Z10; 330; Novelty-Seeking Behavior; Entrepreneurial Traits; Biogeography; Out of Africa Hypothesis; Gene-Culture Co-Evolution; Natural Selection